L’exercice
Exercise is a learning tool in constant use in language learning. But familiarity often leads to hide in construction terms. We will examine different exercise routines to update the choice of the constituents, the organization of the activity, learning principles underlying and reference grammatical descriptions. We try to show at last that the procedure of the exercise, under some conditions, can take place in learning complex tasks like reading here.